Simultaneous Aortic and Pulmonary Valve Replacement in Repaired Congenital Heart Disease - Bobylev, Dmitry; Hysko, Klea; Avsar, Murat; Cvitkovic, Tomislav; Petena, Elena; Sarikouch, Samir; Bleck, Mechthild Westhoff; Hansmann, Georg; Haverich, Axel; Horke, Alexander (The Thoracic and Cardiovascular Surgeon, 2023)
Objectives Patients with congenital heart disease frequently require surgical or percutaneous interventional valve replacement after initial congenital heart defect (CHD) repair. In some of these patients, simultaneous replacement of both semilunar valves is necessary, resulting in increased procedural complexity, morbidity, and mortality. In this study, we analyze the outcomes of simultaneous aortic and pulmonary valve replacements following multiple surgical interventions for CHD.Methods This was a retrospective study of 24 patients who after initial repair of CHD underwent single-stage aortic and pulmonary valve replacement at our institution between 2003 and 2021.Results The mean age of the patients was 28 ± 13 years; the mean time since the last surgery was 15 ± 11 years. Decellularized valved homografts (DVHs) were used in nine patients, and mechanical valves were implanted in seven others. In eight patients, DVHs, biological, and mechanical valves were implanted in various combinations. The mean cardiopulmonary bypass time was 303 ± 104 minutes, and aortic cross-clamp time was 152 ± 73 minutes. Two patients died at 12 and 16 days postoperatively. At a maximum follow-up time of 17 years (mean 7 ± 5 years), 95% of the surviving patients were categorized as New York Heart Association heart failure class I.Conclusion Single-stage aortic and pulmonary valve replacement after initial repair of CHD remains challenging with substantial perioperative mortality (8.3%). Nevertheless, long-term survival and clinical status at the latest follow-up were excellent. The valve type had no relevant impact on the postoperative course. The selection of the valves for implantation should take into account operation-specific factors—in particular reoperability—as well as the patients' wishes.
Keywords: congenital heart disease; aortic valve replacement; pulmonary valve replacement; mechanical valve; valve prosthesis; decellularized homografts